2013
DOI: 10.1111/1467-9604.12028
|View full text |Cite
|
Sign up to set email alerts
|

Misconceptions about traumatic brain injury among students preparing to be special education professionals

Abstract: The researchers performed a survey study to determine the effectiveness of collegiate programmes in dispelling common misconceptions about traumatic brain injury (TBI) while preparing undergraduate and graduate students for special education (SpEd) careers. Respondents included 136 undergraduate and 147 graduate SpEd students in their final semesters before obtaining degrees. Each completed an 18‐item true/false survey about TBI and the associated recovery process. Results were compared with survey responses f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 24 publications
(29 reference statements)
4
24
1
Order By: Relevance
“…These findings are consistent with prior studies (Evans et al, 2009;Hux et al, 2013), where a majority of all participants, including the lay public, replied correctly to the same four statements. In the current study, no statistically significant difference in general knowledge was observed between first and second year graduate students.…”
Section: Chapter 4 Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…These findings are consistent with prior studies (Evans et al, 2009;Hux et al, 2013), where a majority of all participants, including the lay public, replied correctly to the same four statements. In the current study, no statistically significant difference in general knowledge was observed between first and second year graduate students.…”
Section: Chapter 4 Discussionsupporting
confidence: 91%
“…Previous research has shown that misconceptions about TBI, particularly regarding coma, memory loss, and recovery, exist among students preparing to become SLPs and SpEds (Evans et al, 2009;Hux et al, 2013). Misconceptions of concussion have also been observed among licensed school-based SLPs (Duff & Stuck, 2015).…”
Section: Chapter 4 Discussionmentioning
confidence: 99%
See 3 more Smart Citations